2017
DOI: 10.1186/s12872-016-0454-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes and hypertension on cardiovascular outcomes in patients with coronary artery disease receiving percutaneous coronary intervention

Abstract: BackgroundPercutaneous coronary intervention (PCI) is a necessary procedure commonly performed for patients with coronary artery disease (CAD). However, the impact of diabetes and hypertension on long-term outcomes of patients after receiving PCI has not yet been determined.MethodsThe data of 1234 patients who received PCI were collected prospectively, and patients were divided into four groups, including patients with and without DM and those with either DM or hypertension alone. Baseline characteristics, ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 23 publications
4
19
1
Order By: Relevance
“…Previous study found that the prevalence of hypertension was 25% in young CAD patients as compared with 13% in comparable age group without CAD, and the prevalence of hypertension was much higher in elderly CAD individuals as compared with young CAD patients . Several studies also reported an increasing trend of the prevalence of hypertension in young CAD patients . Our results indicate that the prevalence of hypertension is significantly higher in patients with HTB than in patients with LTB (75.0 vs. 17.1%, P < 0.001).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Previous study found that the prevalence of hypertension was 25% in young CAD patients as compared with 13% in comparable age group without CAD, and the prevalence of hypertension was much higher in elderly CAD individuals as compared with young CAD patients . Several studies also reported an increasing trend of the prevalence of hypertension in young CAD patients . Our results indicate that the prevalence of hypertension is significantly higher in patients with HTB than in patients with LTB (75.0 vs. 17.1%, P < 0.001).…”
Section: Discussionsupporting
confidence: 53%
“…36 Several studies also reported an increasing trend of the prevalence of hypertension in young CAD patients. 36,37 Our results indicate that the prevalence of hypertension is significantly higher in patients with HTB than in patients with LTB (75.0 vs. 17.1%, P < 0.001). Moreover, the multiple logistic regression analysis results revealed that hypertension remained as a significant independent risk factor for higher TB after adjustment for age, gender, and body mass index.…”
Section: Determinants Of High Tb In Young Chinese Stemi Patientsmentioning
confidence: 63%
“…Combined DM and CKD seemed to have an additive effect on the progression of atherosclerosis and development of multi-vessel disease than patients with isolated DM or isolated CKD. This is in contrast to a previous study that they observed patients with both DM and hypertension did not have a significant risk of developing multi-vessel disease, as compared with patients with DM alone [ 21 ]. However, in terms of treated numbers of the vessels and lesions, no difference existed among patients with DM alone, CKD alone, or both DM and CKD ( P = NS); thus, dominance of multi-vessel disease and poor left ventricular function in patients with DM and CKD may affect long-term outcomes in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…The past history of diabetes and hypertension are obviously risk factors of ACS (p value <0.05). It is well established that diabetes mellitus is an independent predictor of adverse cardiovascular events, regardless of age [12][13] . In this study smoking has significant association with acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%